Characterization of microbial population of “Alheira” (a traditional Portuguese fermented sausage) by PCR-DGGE and traditional cultural microbiological methods - Albano, A. (2011)
This study evaluates the microbial ecology of ‘Alheira’ by traditional microbiological analysis and a PCR-denaturing gradient gel electrophoresis (DGGE) protocol. Methods and Results: Total microbial DNA from ‘Alheiras’ was extracted directly from the products and subjected to PCR using Eubacterial primers for 16S rDNA. The amplicons were separated by DGGE. The results demonstrated that different products of the same batch display identical profiles, whereas products from different batches of the same producer could display different DGGE profiles. ‘Alheiras’ from different producers were distinguishable based on the respective DGGE profiles. The obtained sequences from prevalent phylotypes affiliated with order Lactobacillales and order Bacillales and class Gammaproteobacteria. The same samples were subjected to traditional microbiological analysis. In both methods, lactic acid bacteria were dominant and were present together with other organisms, mainly members of the family Micrococcaceae. Conclusions: The approach explored in this study allowed the description of the microbial community present in ‘Alheira’ in particular the diversity of lactic acid bacteria. Significance and Impact of the Study: This can be useful for the microbiological characterization of traditional products in order to develop new methods of quality control capable of supporting a standardization of the processes, while preserving their typical traits.